PEMBUATAN DAN PELATIHAN PENGGUNAAN APLIKASI PENCATATAN DATA PAMSIMAS PADA BUM DESA MAKARYO DESA JAGAN KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Sukadi; Candra Budi Susila; Diana Rendrarini (JURNAL DAYA-MAS, 2023)
This community service for creating and training in the use of the Pamsimas data recording application at BUMDes Makaryo was carried out as a form of preparation for Pamsimas managers after Pamsimas was made a Village-Owned Enterprise by the government of Jagan Village, Bendosari District, Sukoharjo Regency. The method of implementing this community service is by making a Pamsimas data recording application and also training in the use of the application or also outreach to Pamsimas managers. With community service activities Creating and Training on the Use of the Pamsimas Data Recording Application it can be concluded that Pamsimas administrators know and understand how to manage customer data and also Pamsimas customer payments using computers or information technology and also in managing Pamsimas data can be done with transparency, fast, precisely , and convenience by using the Pamsimas data recording application